Recurrent phrases in Turkish EFL learners’ spoken interlanguage: A corpus-driven structural and functional analysis - Kızıl, Aysel Şahin; Kilimci, Abdurrahman (My University, 2014)
Various studies contrasting learner language with native speaker (NS) performance have shown that recurrent multiword expressions that come so naturally to the NSs pose difficulty for the non-native (NNS) speakers and hinder their language production although usually easy to understand. Therefore, the present study aims to explore the structural and functional properties of the recurrent phrases in the spoken English of the Turkish learners of English and the native speakers to find out whether these word combinations also cause difficulty for the learners under investigation. The study adopts “the corpus driven ‘recurrent word combination’ method” (De Cock, 2004, p. 227) within the framework of the Contrastive Interlanguage Analysis (CIA) (Granger, 1998). The corpora drawn on in the study are the native speaker corpus, the Louvain Corpus of Native English Conversation (LOCNEC), and the subcorpora of the non-native speaker corpus LINDSEI (the Louvain International Database of Spoken English Interlanguage), which contains speech produced by advanced Turkish learners of English. Two taxonomies were used to analyze the recurrent phrases: the structural taxonomy and the functional taxonomy. The study confirms that the recurrent language characterizes both native and nonnative speech despite marked variations in terms of underuse and overuse phenomena in the learner data. The significance of difference as to the structural and functional variations that particular word combinations display in the nonnative corpus as compared to the native speaker corpus is discussed and pedagogical implications are shared.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Recurrent word combinations; Spoken corpus; Interlanguage; Corpus-driven method; Contrastive interlanguage analysis